2021
DOI: 10.56369/tsaes.3969
|View full text |Cite
|
Sign up to set email alerts
|

Interacción Taninos Vegetales, Microbiota Ruminal Y Metabolismo Del Rumiante

Abstract: <p><strong>Background.</strong> Tannins, as polyphenolic secondary metabolites of plants, are attributed both beneficial and adverse functions when they are consumed by animals, effects that depend on the chemical structure and the concentration used. Among the beneficial properties of tannins, their ability to modulate the ruminal microbiota has been observed, reducing the populations of methanogens and methane (CH<sub>4</sub>) emissions. In addition, effects of tannins have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…CT can generate positive or negative effects on digestion and health in ruminants. This depends on the type, source, dose, molecular weight, and chemical composition of the diet and the adaptability of the animals to its consumption [ 27 , 28 , 45 ]. From these perspectives, the lower potential in situ degradation and in vitro digestibility of DM observed in the T3 and T4 diets ( Table 2 ), is probably due to the increase in tannin levels in response to the increasing incorporation of A. mearnsii and its possible effect on bacteria that degrade nutrients (carbohydrates, proteins and lipids) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT can generate positive or negative effects on digestion and health in ruminants. This depends on the type, source, dose, molecular weight, and chemical composition of the diet and the adaptability of the animals to its consumption [ 27 , 28 , 45 ]. From these perspectives, the lower potential in situ degradation and in vitro digestibility of DM observed in the T3 and T4 diets ( Table 2 ), is probably due to the increase in tannin levels in response to the increasing incorporation of A. mearnsii and its possible effect on bacteria that degrade nutrients (carbohydrates, proteins and lipids) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the greatest limitation in the use of CT is reduced microbial growth and hence a reduced protein supply to the animal [ 26 ]. However, it has been reported that the effect of tannin will depend on CT type, origin, dose, molecular weight and adaptation of the animals to its intake [ 27 , 28 ]. Detrimental effects on animal health show in performance, intake and digestibility.…”
Section: Introductionmentioning
confidence: 99%